Changes in ammonia emmisions in different zonation on closed house in the dry season affects Broiler chicken meat quality - Fahmi Aditya Diyantoro; Teysar Adi Sarjana; Warsono Sarengat (Journal Animal Research and Applied Science, 2019)
This research is an applied research carried out in broiler closed house with the aim of assessing the effect of ammonia emissions levels in different zones which affect the broiler meat quality in the dry season. Seven hundred and twenty broilers which taken from a portion of population in closed house with a capacity of 11.000 were used. The treatment applied is a change in ammonia emissions at a different zones which is measured on 0, 1/4, 1/2, and 3/4 length of broiler house from inlet. The parameters observed were pH, color and Water Holding Capacity (WHC) of broiler chicken meat. The results obtained indicate that an increase in ammonia emissions on zones 3 and 4 significantly affecting the increase of WHC value in zones 3 and 4 while other parameters do not. The increase of WHC value was an indicator of the decrease in broiler meat quality. It was concluded that the increase in ammonia emissions in zones 3 and 4 decreases the meat quality in the form of changes in the value of WHC without affecting pH and color values of broiler chicken breast meat.